2022
DOI: 10.3389/fonc.2022.835957
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Model to Predict Regional Lymph Node Metastasis in Patients With Hepatocellular Carcinoma

Abstract: BackgroundThe evaluation of the nodal status of hepatocellular carcinoma (HCC) is a classic but controversial topic. This study aimed to investigate the incidence of lymph node metastasis (LNM), explore the role of lymph node dissection (LND), and develop and validate a novel model to predict LNM in patients with HCC, not other specified (NOS).MethodsThe study cohort was taken from the Surveillance, Epidemiology, and End Results database. The annual percent change (APC) was calculated using the Joinpoint regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…In the present study, regardless of stage IVA or stage IVB patients, age was significantly associated with early death, which is consistent with the results of previous studies [ 28 , 29 ]. From the SEER database data and the existing research, HCC is obviously more likely to occur in males [ 30 ]; however, gender was not a risk factor for early death of advanced HCC patients.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, regardless of stage IVA or stage IVB patients, age was significantly associated with early death, which is consistent with the results of previous studies [ 28 , 29 ]. From the SEER database data and the existing research, HCC is obviously more likely to occur in males [ 30 ]; however, gender was not a risk factor for early death of advanced HCC patients.…”
Section: Discussionsupporting
confidence: 93%
“…In the last decades, thanks to better etiological monitoring and management, especially the progress of viral hepatitis prevention and therapy, the morbidity of HCC has shown a trend of decelerated growth and is even gradually decreasing both in the East and West. Nevertheless, HCC is still a heavy health burden worldwide (1)(2)(3)(4)(5)(6)(7). According to a national survey in the USA, HCC ranks 5th and 7th in estimated new cancer deaths for male and female patients in 2022, respectively (1).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, we observed that early-onset patients were inclined to be unmarried, with larger tumor size and worse histological grade than late-onset patients. Furthermore, it has been demonstrated that unmarried status [ 23 ], large tumor diameter [ 24 ], and poor tumor differentiation [ 25 ] were considered independent risk factors for HCC metastasis, which could partially explain why early-onset HCC was prone to experience DM. On the other hand, the lack of suspicion of HCC in the younger patient population has led to delays in seeking medical attention and diagnosing the condition.…”
Section: Discussionmentioning
confidence: 99%